An AMUSING look at the host of the periodic nuclear transient ASASSN-14ko reveals a second AGN. Issue 4 (22nd July 2021) - Tucker, M A; Shappee, B J; Hinkle, J T; Neustadt, J M M; Eracleous, M; Kochanek, C S; Prieto, J L; Payne, A V; Galbany, L; Anderson, J P; Auchettl, K; Auge, C; et al.
ABSTRACT: We present Multi-Unit Spectroscopic Explorer (MUSE) integral-field spectroscopy of ESO 253−G003, which hosts a known active galactic nucleus (AGN) and the periodic nuclear transient ASASSN-14ko, observed as part of the All-weather MUse Supernova Integral-field of Nearby Galaxies survey. The MUSE observations reveal that the inner region hosts two AGN separated by 1.4± 0.1 kpc (≈1_.^′′ 7). The brighter nucleus has asymmetric broad permitted emission-line profiles and is associated with the archival AGN designation. The fainter nucleus does not have a broad emission-line component but exhibits other AGN characteristics, including v_FWHM ≈ 700 km s^-1 forbidden line emission, _10([O III]/Hβ) ≈ 1.1, and high-excitation potential emission lines, such as [Fe vii ] λ6086 and He ii λ4686. The host galaxy exhibits a disturbed morphology with large kpc-scale tidal features, potential outflows from both nuclei, and a likely superbubble. A circular relativistic disc model cannot reproduce the asymmetric broad emission-line profiles in the brighter nucleus, but two non-axisymmetric disc models provide good fits to the broad emission-line profiles: an elliptical disc model and a circular disc + spiral arm model. Implications for the periodic nuclear transient ASASSN-14ko are discussed.